Frictional Behavior Downdip Along the Subduction Megathrust: Insights From Laboratory Experiments on Exhumed Samples at In Situ Conditions. Issue 1 (30th December 2022) - den Hartog, S. A. M.; Marone, C.; Saffer, D. M.
Abstract: Subduction megathrusts exhibit a spectrum of slip modes, including catastrophic earthquakes. Although the mechanical and frictional properties of materials sampled from subduction zones have been studied extensively, few datasets have been collected for compositions and at pressure and temperature conditions representative of those in situ. The Nankai subduction zone in southwest Japan is a well‐studied margin, and abundant data provide an opportunity to advance our understanding of fault and earthquake physics. Here, we use samples exhumed in the Shimanto and Sanbagawa Belts on Shikoku Island of southwest Japan that represent analogs for materials along the present‐day megathrust at depths of ∼5–>25 km, and we shear these at their peak in situ pressure‐temperature ( P‐T ) conditions. Effective normal stresses range from 28 to 192 MPa, and temperatures from 105°C to 470°C. We used pore fluid pressures of 45–240 MPa, corresponding to fluid overpressure ratios λ of 0.65 and 0.90. Slip velocities of 0.1–100 μm/s were used, in order to focus on the nucleation of instability and earthquakes. We found predominantly velocity‐strengthening (inherently stable) behavior under all conditions for λ  = 0.65. For λ  = 0.90, velocity‐weakening behavior was observed at 350°C, with velocity‐strengthening behavior at lower and higher temperatures. The rate/state frictional stability parameter ( a ‐ b ) increases with slip velocity at temperatures up to ∼200°C and remains constant or decreases with slip velocity at higher temperatures. Overall, our results demonstrate the potentially important roles of both temperature and slip velocity in controlling the distribution of stress and frictional rheology along subduction thrusts. Plain Language Summary: The largest earthquakes on Earth occur along fault zones at subduction plate boundaries. These earthquakes are controlled, in large part, by the frictional properties of the fault zone materials. However, those properties are not fully understood, and laboratory experiments are key to advancing our knowledge. One example of a subduction zone is the Nankai Trough in southwest Japan. This subduction zone has been the subject of several drilling expeditions, recovering samples from the subsurface, and providing materials used in laboratory experiments. However, the experiments to date focus on materials recovered from depths shallower than those where earthquakes nucleate, and have been performed at temperatures lower than those in earthquake source regions. In this study, we used samples known to come from depths where earthquakes nucleate, and we performed friction experiments at temperatures and pressures relevant for these depths. We find that the frictional properties are primarily dependent on temperature and on the velocity of sliding. Key Points: Friction experiments on samples exhumed in the Shimanto Belt and Sanbagawa Belt at sample‐specific in situ peak PT conditions Behavior predominantly velocity‐strengthening with velocity‐weakening at 350°C Frictional slip stability shows temperature‐dependent trend with slip velocity